Primary Cecal Squamous Cell Carcinoma: A Case Report of a Rare Tumor with Poor Prognosis - Mohamed Bouzroud; Mustapha Azzakhmam; Aboulfeth El Mehdi; Bouchentouf Sidi Mohammed; El Kaoui Hakim; Oukabli Mohaned; Bounaim Ahmed (Case Reports in Oncological Medicine)
Squamous cell carcinoma of the colon is a rare tumor and primary cecal localization is unusual. This malignant condition is marked by a worst prognosis due to early local invasion. We report a case of a 46-year-old female patient admitted to the emergency department with symptoms of peritonitis. CT scan showed a cecal tumor perforated in the retroperitoneal space. The patient underwent right hemicolectomy with D2 lymphadenectomy without intestinal anastomosis. The diagnosis of squamous cell carcinoma was confirmed by histopathological examination. Squamous cell carcinoma is a malignant tumor with poor prognosis, hence, the interest of early diagnosis and management.